PENGARUH TERAPI BERKEBUN TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI PANTI SOSIAL TRESNA WERDHA MINAULA KENDARI - Magfirah, Magfirah; Fariki, la ode Ali (Universitas Islam Negeri Alauddin Makassar, 2018)
The Human aging and the decline of physiological occur in the elderly due to degenerative process. Non-communicable diseases such as hypertension is often suffered by the elderly. Gardening therapy is one of the methods that can be used as an alternative to normalize the blood pressure. The purpose of this research is to examine the effects of gardening therapy on the changes in elderly blood pressure with hypertension.The research design used Quasy experimental pre post test with control group and the total sample of 15 respondents are selected by using purposive sampling. The independent variable in this study is the gardening therapy and the dependent variable is the systolic and diastolic blood pressure as measured by sphygmomanometer and stethoscope. The data were analyzed by using paired t-test and independent t-test (α = 0.05). The results of bivariate analysis in this study showed that there was an effect of the gardening therapy on the changes in systolic and diastolic blood pressure in the first, third, and fourth measurements, while for systolic diastolic which was described by the following p value, p1 = 0.005, p3 = 0.015, p4 = 0.017 and p3 = 0.018 and p4 = 0.025. The analysis of difference in the four meetings showed that there were differences between control group and systolic blood pressure between the control group and the intervention at the third meeting at Institusi Sosial Tresna Werdha Minaula Kendari which was represented by the following p value, p3 TDS = 0.045. The conclusion of this study is that the gardening therapy is an effective way to normalize the blood of elderly people with hypertension, so it is necessary to do the therapy as an alternative non-pharmacological therapy that can be done independently or together without causing side effects.Key Words: Gardening therapy, elderly blood pressure.